Essential fatty acid content in the ethnozoological products used in the folklore medicines by the Tangkhul tribe of the North East India - Singh, Oinam Ibochouba; Ahongshangbam, Rhea; Nillapriya, Laishram; Devi, Keisham Shanta; Singh, Kshetrimayum Birla (Edelweiss Applied Science and Technology, 2024)
Tangkhul tribes are main habitant of the Ukhrul district of Manipur, a north eastern state of India and popular for using the products of animal fauna in the folklore medicines for curing certain human ailments. To our knowledge, no investigation has been done on the essential fatty acids content in the animal products used in the traditional medicines by the Tangkhul tribe of Manipur. The objective of the study is to determine the essential fatty acids concentration in the selected ethnozoological products namely, Periplaneta americana, Upupa epops, Scolopendra gigantea, Pheretima posthuma, Hoplobatrachus tigerinus, Sus scrofa domesticus, and Tylototriton verrucosus by Fatty Acid Methyl Esters (FAME) methods. The result of the study revealed that unsaturated fatty acids are found to be contained generally higher than saturated fatty acids in the seven-ethnozoological products studied. Among the monounsaturated fatty acids, Oleic Acid (7579.19 ± 70.23 mg/100g) is found to be highest in concentration and is recorded in the P. americana. Some of the common essential PUFAs recorded in the samples of the ethnozoological products studied were Linolenic Acid, Linoleic acids, Erucic Acid, Oleic Acid, Elaidic Acid, Palmetoleic Acid, Myristoleic Acid etc. with the highest concentration of linolenic acid (5518.03mg/100g) found in the P. americana. The used of seven ethnozoological products mentioned per se by Tangkhul Tribes of Manipur in their folklore medicines for the treatment of various human ailments may be attributed to the presence of various polyunsaturated fatty acids especially high amount of omega-3 fatty acids, palmetoleic acid, ecosapentanoic acid in them.